THE USE OF HISTORICAL SITES IN TERNATE AS LEARNING SOURCES - Jamin Safi; Suharlin Ode Bau (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
This research aimed to describe the use of historical sites in Ternate as learning sources. To achieve the mentioned aim, this research applied the qualitative method. As a field study, the data collection was done through interviews, observations, and content analysis. The data was validated by using triangulation to acquire accurate information. The learning of history in the subject of historical heritage was done by exploring the historical heritage in Ternate. The exploration was done after the discussion between the lecturer and the students. The field study was done with the project method and study tour. The process of field study covered learning orientation, historical site exploration, report writing, and students’ presentation. During exploration, the students observed, noted, and interpreted the historical heritages in the sites. The field study can promote the students to think about the chronology of any historical event. By doing this study, the students' historical awareness can also be grown.